2016
DOI: 10.11607/prd.2854
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Use of Laser-Microtextured Abutments: A Case Series

Abstract: This article discusses the clinical use of laser-microtextured abutments on dental implant restorations. Four cases are presented, each using one of the four commercially available laser-microtextured abutment styles. Numerous preclinical and clinical studies have shown the positive effects of laser microtexturing on the implant platform in limiting crestal bone loss and benefiting soft tissue stability. Other histologic studies of laser microtexturing on the implant abutment have demonstrated the ability of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 9 publications
(4 reference statements)
2
9
0
Order By: Relevance
“…A Systematic review (Iglhaut et al., 2014) stated that the micro‐grooved surface could be associated with a longer connective tissue attachment and minor bone resorption around implants. In agreement with these findings, some studies have recently shown that a modified prosthetic abutment surface promotes the creation of a more robust perpendicular collagen fiber attachment to the abutment at the early stage (Nevins et al., 2012a; Nevins et al., 2012b; Shapoff et al., 2016).…”
Section: Introductionmentioning
confidence: 54%
“…A Systematic review (Iglhaut et al., 2014) stated that the micro‐grooved surface could be associated with a longer connective tissue attachment and minor bone resorption around implants. In agreement with these findings, some studies have recently shown that a modified prosthetic abutment surface promotes the creation of a more robust perpendicular collagen fiber attachment to the abutment at the early stage (Nevins et al., 2012a; Nevins et al., 2012b; Shapoff et al., 2016).…”
Section: Introductionmentioning
confidence: 54%
“…After duplicates were discarded, 63 records remained. Review of the titles and abstracts resulted in 22 articles identified as full‐text articles, and seven were excluded for the following reasons: follow‐up <12 months; 44 , 45 redundant studies; 32 LMS design not only in implant neck; 21 , 46 performed with additional surgeries such as hard 47 or soft tissue 48 augmentation. Finally, 15 eligible articles 21‐31,33‐36 were included in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Abutments as transmucosal parts of an implant are expected to achieve early soft-tissue adhesion, demonstrating good soft-tissue biocompatibility. Modifications of implant abutment surfaces have been the focus of recent research [10,11,12].…”
Section: Introductionmentioning
confidence: 99%